An Attempt to Determine the CSR Potential of the International Clothing Business - Laudal, Thomas (Journal of business ethics, 2010)
Most empirical studies of corporate social responsibility (CSR) focus on variables at the company level. In this article, I focus on the sector level: I consider features of the international clothing business and of the global economy in general, that may influence the CSR potential. There is high ‘CSR potential’ when sector-specific features indicate that the risk of violating CSR standards is high. Thus, ‘high CSR potential’ indicates that there is a potential for positive influence through CSR-related actions. Based on several empirical studies of the clothing business, I identify six features that indicate a high CSR potential. These features are shown to be consistent with more general features of the global economy. This holds whether we emphasize asymmetric relations and unequal distribution, the product cycle, or transnationalization. Thus, the CSR potential of the international clothing business seems not only to be a product of sector-specific properties, but also of more systemic and general features of the global economy. This suggests that the CSR performance of individual companies may enhance their social and environmental impact, but will probably have little effect on the features that determine the CSR potential. In order to affect these features I argue, we rely on other institutions to act – mainly governments. Finally, I conclude that this study shows that it is useful to identify the CSR potential of a business sector. We get a picture of which part of the international CSR standards companies run the greatest risk of violating and of which structural issues intergovernmental actions should address to reduce the potential for violating CSR standards.